Newborn sex-specific transcriptome signatures and gestational exposure to fine particles: findings from the ENVIRONAGE birth cohort - Ellen Winckelmans; Karen Vrijens; Maria Tsamou; Bram G. Janssen; Nelly D. Saenen; Harry A. Roels; Jos Kleinjans; Wouter Lefebvre; Charlotte Vanpoucke; Theo M. de Kok; Tim S. Nawrot (BMC, 2017)
Abstract Background Air pollution exposure during pregnancy has been associated with adverse birth outcomes and health problems later in life. We investigated sex-specific transcriptomic responses to gestational long- and short-term exposure to particulate matter with a diameter < 2.5 μm (PM2.5) in order to elucidate potential underlying mechanisms of action. Methods Whole genome gene expression was investigated in cord blood of 142 mother-newborn pairs that were enrolled in the ENVIRONAGE birth cohort. Daily PM2.5 exposure levels were calculated for each mother's home address using a spatial-temporal interpolation model in combination with a dispersion model to estimate both long- (annual average before delivery) and short- (last month of pregnancy) term exposure. We explored the association between gene expression levels and PM2.5 exposure, and identified modulated pathways by overrepresentation analysis and gene set enrichment analysis. Results Some processes were altered in both sexes for long- (e.g. DNA damage) or short-term exposure (e.g. olfactory signaling). For long-term exposure in boys neurodevelopment and RhoA pathways were modulated, while in girls defensin expression was down-regulated. For short-term exposure we identified pathways related to synaptic transmission and mitochondrial function (boys) and immune response (girls). Conclusions This is the first whole genome gene expression study in cord blood to identify sex-specific pathways altered by PM2.5. The identified transcriptome pathways could provide new molecular insights as to the interaction pattern of early life PM2.5 exposure with the biological development of the fetus.